Sokrat sanja o objektu - Justin, Janez (Monitor ISH, 2007)
As any other realistic theory of knowledge, Platoćs version assumes that what we know about an object exists independently of our intellect. Therefore Platohas to answer two standard questions, the first referring to the properties of the object and the second to the conditions under which the latter can be accessed by the intellect. The article shows that Plato's late work Theaetetus presents some answers largely ignored by his commentators. Theobject of knowledge is recognised to possess permanence and a stable identity; moreover, its identification is attributed an indexical quality not only in Theaetetus, but also in Cratylus, Timaeus, and the Sophist. The history of philosophy has thus overlooked that Plato was the first to develop the concepts of indexical discourse and indexical knowledge.
Keywords: Plato, 427-347 pr.n.št.; analitična filozofija; Main Agency of Automobiles and Tanks of the Ministry of Defense of the Soviet Union; objekt; indeksikalni govor; teorija vednosti